(31)P Nuclear Magnetic Resonance Spectroscopy of Native and Recombined Lipoproteins - Assmann, Gerd (1974)
Native and recombined lipoproteins have been studied by (31)P nuclear magnetic resonance spectroscopy. Very low-, low-, and high-density lipoproteins exhibited characteristic spectra. The main resonances were assigned to phosphatidylcholine and sphingomyelin. Relaxation times for these phospholipids were separately measured in low-density lipoproteins and high-density lipoproteins. The effect of paramagnetic ions (Eu(+++)) on the nuclear magnetic resonance spectrum of high-density lipoproteins is reported.